(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to demonstrate the supervisory role of the Central Bank of Iraq to limit the phenomenon of money laundering implemented through electronic payment tools, especially prepaid cards, and the research was based on a main hypothesis that the supervisory control of the Central Bank of Iraq limits money laundering operations implemented through electronic payment tools, and to reach the objectives of the research and to prove its hypothesis, a checklist was prepared consisting of (55) paragraphs distributed in (7) axes, the paragraphs were drafted by relying on the instructions of the rules of due diligence for financial institutions for non-financial businesses and professions specified towards customers No. (1) of 2023, the Electronic Payment Services Regulation No. (2) of 2024 and a number of controls, instructions and circulars issued by the Central Bank of Iraq and the AML/CFT Office, as well as using the experiences of some Arab countries, the results of the checklist were analyzed using a seven-point Likert scale (fully applied fully documented, fully applied partially documented, fully applied not documented, partially applied fully documented, partially applied partially documented, partially applied not documented, not applied not documented), and using frequencies, weighted arithmetic mean equations, percentage of conformity and gap size for each axis as methods to analyses the results, The researchers reached a set of conclusions, the most important of which are that the Central Bank of Iraq allows electronic payment companies to issue and reload prepaid cards with relatively high limits, which increases the risk of exploiting these cards in money laundering operations and the reliance of these companies on the ‘Light KYC’ form when issuing and reloading these cards, which indicates a weakness in customer identification procedures. In addition to the difficulty of monitoring the movement of financial transactions carried out through prepaid cards issued by electronic payment companies because they are not linked to a bank account. Therefore, the researchers recommend a set of recommendations, the most important of which is the need for the Central Bank of Iraq to reduce the maximum limit for issuing and reloading prepaid cards issued by electronic payment companies to minimize the risk of money laundering through them.